2018
DOI: 10.1186/s13287-017-0760-6
|View full text |Cite|
|
Sign up to set email alerts
|

Human umbilical cord mesenchymal stem cell conditioned medium attenuates renal fibrosis by reducing inflammation and epithelial-to-mesenchymal transition via the TLR4/NF-κB signaling pathway in vivo and in vitro

Abstract: BackgroundRenal fibrosis is characterized by infiltration of interstitial inflammatory cells and release of inflammatory mediators, activation and proliferation of fibroblasts, and deposition of excessive extracellular matrix (ECM). The aim of this study was to evaluate the effect of human umbilical cord-derived mesenchymal stem cell (hucMSC) conditioned medium (CM) on renal tubulointerstitial inflammation and fibrosis.MethodsRenal interstitial fibrosis was prepared in vivo using the unilateral ureteral obstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 31 publications
(38 reference statements)
3
69
0
3
Order By: Relevance
“…As acquired immune cells, B cells secrete cytokines such as transforming growth factor-β1 (TGF-β1), tumor necrosis factor-α (TNF-α), interleukin-1 (IL-1), and interleukin-6 (IL-6), which promotes brosis progression. A large number of studies have shown that cytokines were involved in an in ammatory response and the brosis process of kidney, liver, and lung tissues [30,31]. In recent years, there have been reports on the involvement of B cells in the myocardial brosis process of cardiovascular diseases, but the mechanism of B cells and their cytokines in the myocardial infarction process after AMI is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…As acquired immune cells, B cells secrete cytokines such as transforming growth factor-β1 (TGF-β1), tumor necrosis factor-α (TNF-α), interleukin-1 (IL-1), and interleukin-6 (IL-6), which promotes brosis progression. A large number of studies have shown that cytokines were involved in an in ammatory response and the brosis process of kidney, liver, and lung tissues [30,31]. In recent years, there have been reports on the involvement of B cells in the myocardial brosis process of cardiovascular diseases, but the mechanism of B cells and their cytokines in the myocardial infarction process after AMI is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The cell-free CM derived from MSCs is enriched in various soluble factors, including growth factors, immunomodulatory molecules, cytokines, and chemokines [40,48,49]. MSC-derived CM has shown to have beneficial effects both in vivo and in vitro [50][51][52][53]. In addition, preconditioning strategies such as the environmental variations and stimulatory conditions of MSCs can change the composition of CM active factors and influence the CM's therapeutic effect.…”
Section: Msc-derived CMmentioning
confidence: 99%
“…MSCs can differentiate into several types of cells including endothelial cells, myocytes, keratinocytes, and fibroblasts . Moreover, stem cells produce several anti‐inflammatory and antifibrotic mediators, and secrete factors that create a regenerative microenvironment . Cord blood stem cells embedded in a scaffold secrete for example MMP‐9, mediating collagen degradation in uterine scars, which improves the regeneration of the endometrium, myometrium and blood vessels .…”
Section: Umbilical Cord: From Waste Materials To Source Of Therapeuticmentioning
confidence: 99%
“…[127][128][129] Moreover, stem cells produce several anti-inflammatory and antifibrotic mediators, and secrete factors that create a regenerative microenvironment. [130][131][132][133] Cord blood stem cells embedded in a scaffold secrete for example MMP-9, mediating collagen degradation in uterine scars, which improves the regeneration of the endometrium, myometrium and blood vessels. 134 Administered cord blood stem cells also promote the recruitment of endogenous stem cells.…”
Section: Umbilical Cord: From Waste Materials To Source Of Therapeutmentioning
confidence: 99%